Hospitalized burden and outcomes of coccidioidomycosis: A nationwide analysis, 2005–2012. (4th October 2016) - Luo, Ruihong; Greenberg, Alan; Stone, Christian D.
Abstract: The incidence of coccidioidomycosis (CM) infection has increased over the last 20 years. We investigated recent trends of CM-associated hospitalization in the United States. patients with CM-associated hospitalization were identified from the Nationwide Inpatient Sample, 2005–2012. The outcomes of interest were the trend of annual hospitalization, in-hospital mortality, and independent risk factors for mortality. A total of 30, 870 hospitalizations with CM (29, 584 of adults; 1, 286 of children) were identified. Over the 8-year study period, the number of hospitalizations for CM fluctuated but increased overall with successively higher peaks in 2009 and 2011. The annual median length of stay (LOS) shortened from 6 to 7 days in 2005–2010 to 4 days in 2011 and 5 days in 2012. The inflation-adjusted hospital charges were highest in 2006 then trended down by 21% in 2012. The in-hospital mortality declined from the highest level in 2005 (5.2%) to a low in 2010 (1.1%), then increased modestly in 2011 (1.9%) and 2012 (1.5%). Hospitalizations were identified in 46 states, with nearly half in Arizona (49.1%), followed by California (36.8%), Texas (3.3%), and Nevada (1.6%). Logistic regression analysis in adults revealed that in-hospital mortality was associated with age groups 61–70 years and >70 years (OR = 3.3 and 3.5, respectively. Ref: 18–30 years) and Charlson Index ≥1 (OR = 2.0–8.3). In children, males had lower risk for mortality than females (OR = 0.2). This study shows that CM-associated hospitalizations occur widely throughout the United States with an increasing admission trend; however, patient outcomes have improved and the cost of hospitalization has decreased.